Tillandsia guatemalensis (Bromeliaceae), un registro nuevo en la flora de Costa Rica - Morales, J. Francisco (2016)
T i l l a n d s i a g u a t e m a l e n s i s , i s r e p o r t e d f o r f i r s t t i m e i n C o s t a R i c a . I t s r e l a t i o n s h i p s w i t h o t h e r species are discussed. In addition, a key for these species is given.